2021
DOI: 10.3168/jds.2020-19638
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis on infrared-predicted milk minerals for Danish dairy cattle

Abstract: 0.63, and a relative error of 18.8%. Prediction accuracies of milk minerals based on infrared-predicted fat, protein, and lactose content were considerably lower than those based on the infrared milk spectra. This shows that the milk infrared spectrum contains valuable information on milk minerals, which is currently not used. Heritability for infrared-predicted Ca, Na, and P varied from low (0.13) to moderate (0.36). Several QTL for infrared-predicted milk minerals were observed that have been associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Soyeurt et al (2011) suggested that models with R 2 > 0.75 might be utilized for animal breeding. However, Zaalberg et al (2021) used prediction models with R 2 > 0.6 for mineral elements in animal breeding [ 31 ]. Cecchinato et al (2009) showed low R 2 values for curd characteristics predicted by MIRS, but they found high genetic correlations between the measured values and the predicted values [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soyeurt et al (2011) suggested that models with R 2 > 0.75 might be utilized for animal breeding. However, Zaalberg et al (2021) used prediction models with R 2 > 0.6 for mineral elements in animal breeding [ 31 ]. Cecchinato et al (2009) showed low R 2 values for curd characteristics predicted by MIRS, but they found high genetic correlations between the measured values and the predicted values [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another difference is clearly exposed by Zaalberg et al [26], and a mean difference is observed for Danish Holstein with −4.09%, 5.07%, 8.08%, −29.32%, and −5.49% and for Danish Jersey with 12.35%, 23.71%, 17.91%, −13.61%, and −14.49% for Na, Ca, Mg, P, and K, respectively, in comparison to our data.…”
Section: Reference Datasetmentioning
confidence: 92%
“…Consequently, there is a need to assess the mineral profile in milk through costeffective and large-scale methods, such as milk MIR spectrometry. From 2009 and the first study conducted by Soyeurt et al [19], numerous studies were carried out to develop MIR models predicting milk minerals [20][21][22][23][24][25][26]. For wide, large-scale use by dairy herd improvement (DHI) centers and dairy industries, such models need to be robust to provide accurate and reproducible predictions in various conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possible threat represents a restriction for the estimation of accurate genetic parameters for milk minerals, as well as being able to obtain high accuracy estimates of genetic merit for individual animals (Visentin et al ., 2019). Therefore, infrared prediction of milk minerals could be a very important and cheap addition to the collection of milk traits that are presently accessible for farm management and breeding programs (Zaalberg et al ., 2021).…”
mentioning
confidence: 99%